HUBUNGAN POLA KOMUNIKASI KELUARGA DAN MANAJEMEN WAKTU TERHADAP INDEKS PRESTASI MAHASISWA TINGKAT II JURUSAN D-III KEBIDANAN UNIVERSITAS BATAN TAHUN 2017 - Putrianti, Rika Decita; Mona, Silvia (Universitas Batam, 2018)
Patterns of family communication as a form of interaction between parents and children and between family members have an implication to the process of emotional development. Meanwhile, time management is one of the important approach in achieving academic achievement. The purpose of this research is to know the correlation of communication pattern and time management toward student achievement ondex, the research method is analytic, using cross sectional design. Populais research is a student level II, conducted in May 2017. Sampling in total sampling sebanayak 38 respondents. The result of this research is 5 respondents (13,2%), communication pattern is not good with GPA 3 respondent (7,9%) and communication pattern good 33 responden (84,3%) with GPA 35 respondent (92,1%) poor management time 6 respondents (15,8%) with GPA 3 respondent (7,9%) and good time management 32 respondents (84,3%) with GPA 35 respondent (92,1%). The conclusion of this research is there is no significant relationship between family communication pattern and time management toward student achievement index.Â